2009
DOI: 10.3233/wor-2009-0810
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue factors affecting metropolitan bus drivers: A qualitative investigation

Abstract: Metropolitan bus drivers daily face work in a stressful and draining work environment, exposing them to the serious risk of driver fatigue. However, there has been a dearth of information exploring the unique antecedents and effects of such fatigue. To date, much of the research into metropolitan bus drivers has been under the umbrella of large heavy vehicle driving studies, which include a disproportionally large population of long-haul drivers, who are likely to face a significantly different set of fatigue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…The mean scores of perceived stress (PSS-10) obtained in out cohort are comparable with data from similar studies in samples of drivers in other countries and can be considered quite low [23,[27][28][29]. Regarding the scores of questionnaires investigating personality traits (EPQ-R and IVE) and stress perception during driving (DSI), our data is also comparable with similar studies.…”
Section: Discussionsupporting
confidence: 89%
“…The mean scores of perceived stress (PSS-10) obtained in out cohort are comparable with data from similar studies in samples of drivers in other countries and can be considered quite low [23,[27][28][29]. Regarding the scores of questionnaires investigating personality traits (EPQ-R and IVE) and stress perception during driving (DSI), our data is also comparable with similar studies.…”
Section: Discussionsupporting
confidence: 89%
“…Vehicle operators in the transport sector industry may belong to the occupational group with the highest prevalence of job stress rates [ 4 , 5 ], and many environmental variables associated with the job of professional drivers, especially those working in the field of public transportation, have been addressed by different studies as typically adverse [ 6 , 7 ]. Several factors such as continuous time pressure, excessive physical demands, environmental overstimulation, problematic interactions with other road users, lack of social support at work, and irregular shifts [ 8 , 9 ] have been characterized as potential stress-related factors, which at the same time enhance the potential occurrence of negative outcomes in terms of health, safety, and performance [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long and irregular hours are common, creating difficulties for family meals [23], constraining time available for meal preparation and exercise [22], and potentially limiting access to healthy foods [26]. While previous research has examined associations between long work hours and outcomes such as back and neck pain [27], occupational fatigue [28,29], and psychological health [30] in transportation workers little to no research has examined associations with weight and weight-related behaviors in this occupational group. The present study examined associations between work hours and behavioral variables and among men and women as prior research has identified gender differences between work hours, health behaviors and obesity [7,9,31].…”
Section: Introductionmentioning
confidence: 99%